2014
DOI: 10.1002/cite.201400078
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Microbiology and Biotechnology: Progress and Prospects

Abstract: Environmental microbiology and biotechnology are crucial in the modern society. They influence human health, environment and serve as a source of energy and provider of novel bioproducts. The key areas of interest are bioremediation, microbial communities, pathogen detection, wastewater treatment, energy generation, bioprocesses, and natural product discovery. Environmental microbiology must interact with hydrology, biogeochemistry, limnology, oceanography and numerical modeling. This subject will continue to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 215 publications
(284 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, Environmental Engineering education in Turkey is separated from Civil Engineering education, and it is taught as a separate department according to the needs of specialist engineers for environmental problems in the country . Environmental engineers also benefit from hydraulics, chemistry, machinery, and biology for various research areas such as water and wastewater treatment technologies , air pollution control , noise control , solid and hazardous waste management , recycling technologies , sludge disposal , incineration systems , environmental microbiology , environmental impact assessment , production of electricity from wastewater with fuel cells , biogas production , and cleaner production technologies .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Environmental Engineering education in Turkey is separated from Civil Engineering education, and it is taught as a separate department according to the needs of specialist engineers for environmental problems in the country . Environmental engineers also benefit from hydraulics, chemistry, machinery, and biology for various research areas such as water and wastewater treatment technologies , air pollution control , noise control , solid and hazardous waste management , recycling technologies , sludge disposal , incineration systems , environmental microbiology , environmental impact assessment , production of electricity from wastewater with fuel cells , biogas production , and cleaner production technologies .…”
Section: Introductionmentioning
confidence: 99%
“…Microbial bioremediation is a technology insufficiently recognized, although several studies have confirmed its benefits. The use of microorganisms to remove, convert or transform environmental contaminants into safe compounds from various environmental matrices is becoming an attractive technology, not only for the scientific community, but also for entrepreneurs [12][13][14][15][16].…”
mentioning
confidence: 99%